2019
DOI: 10.33448/rsd-v8i10.1420
|View full text |Cite
|
Sign up to set email alerts
|

Re-designing the Higher Order Thinking Skills (HOTS) Approach for Academic Writing Students

Abstract: This study was conducted to identify learning requirements, objective condition, and learning design of academic writing based on Higher Order Thinking Skills (HOTS) approach which took in Language and Arts Faculty in Jakarta State University. It used qualitative, quantitative approach and ground method with the procedure includes conducting initial research (pre-development), designing academic writing learning design, examining and revising the result of academic writing learning design and effectiveness exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This is focused on the idea that students would go beyond their comprehension of certain content to apply their critical reasoning as well (Singh et al, 2020). The learning of writing process also supports students' desire to think critically and creatively differently (Lustyantie et al, 2019). This means In general, this finding proved that the process-genre approach gave positive impact on improvement of students' writing ability and HOTs.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This is focused on the idea that students would go beyond their comprehension of certain content to apply their critical reasoning as well (Singh et al, 2020). The learning of writing process also supports students' desire to think critically and creatively differently (Lustyantie et al, 2019). This means In general, this finding proved that the process-genre approach gave positive impact on improvement of students' writing ability and HOTs.…”
Section: Discussionmentioning
confidence: 82%
“…The study of the instructor's perspective states that they have used various strategies that can help learners increase HOTs through real-life situations and problem-solving skills (Singh et al, 2020). Research & development in learning to write by integrating HOTs was also carried out by several researchers to create valid, practical, and effective learning products in the form of syllabus, modules, and textbooks (Lustyantie et al, 2019;. Besides, another study revealed that HOTs questions were able to improve the descriptive text writing skills of grade 8 junior high school students (Sianturi et al, 2020).…”
Section: Introductionmentioning
confidence: 99%